2020
DOI: 10.1177/0300060520901872
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intracuff lidocaine in reducing coughing on tube: a systematic review and meta-analysis

Abstract: Objective: To investigate the efficacy of intracuff lidocaine in reducing coughing and other endotracheal tube side effects and so ensure a smooth extubation process. Method: PubMed, EMBASE, and Cochrane Library databases were systematically searched for all randomised controlled trials (RCTs) published before June 30, 2019 that investigated the efficacy of intracuff lidocaine, with or without sodium bicarbonate, in reducing coughing and other complications related to endotracheal intubation. A random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Thirdly, regardless of whether lubricating the cuff before intubation may have an important impact on postoperative airway complications in patients undergoing endotracheal intubation, it is necessary to analyze lubrication of the cuff before intubation in order to eliminate the influence of confounding factors on the results. Finally, 12 RCTs were included in this study, while the previous study only included 9 RCTs[ 36 ] and 8 RCTs[ 37 ] in the alkalized lidocaine subgroup. Additional trials will provide more data and information to support the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, regardless of whether lubricating the cuff before intubation may have an important impact on postoperative airway complications in patients undergoing endotracheal intubation, it is necessary to analyze lubrication of the cuff before intubation in order to eliminate the influence of confounding factors on the results. Finally, 12 RCTs were included in this study, while the previous study only included 9 RCTs[ 36 ] and 8 RCTs[ 37 ] in the alkalized lidocaine subgroup. Additional trials will provide more data and information to support the conclusions of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that intracuff alkalinized lidocaine decreased postoperative airway complications. To achieve a significant therapeutic effect, large doses of lidocaine may be necessary without alkalinization[ 37 ]. According to Estebe et al [ 34 ], plasma lidocaine levels confirmed the increased diffusion of lidocaine through the cuff when lidocaine was alkalinized.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these pharmacologic aids may not have the same efficacy in high-risk patients. Despite these limiting factors, we discuss some of the more widely studied medications below ( Table 2 ) [ 13 , 15 , 34 36 , 45 , 47 , 53 56 , 59 63 ]. Other pharmacologic agents, such as ketamine, have been used to achieve smooth emergence [ 64 ].…”
Section: Pharmacologic Aids Of Tracheal Extubationmentioning
confidence: 99%
“…Alkalinization or a combination of warming and alkalinization of the anesthetic can increase the proportion of the uncharged drug available for diffusion, thereby increasing the rate of diffusion [ 67 ]. Many studies have demonstrated the efficacy of intracuff lidocaine in decreasing cough and sore throat [ 53 – 55 ]. Two systematic reviews and meta-analyses demonstrated that both alkalinized and nonalkalinized intracuff lidocaine showed significant reduction of postoperative sore throat, coughing, and dysphonia compared to control groups without intracuff lidocaine [ 53 , 54 ].…”
Section: Pharmacologic Aids Of Tracheal Extubationmentioning
confidence: 99%
“…Recently, several pharmacological and non-pharmacological approaches for the prevention of POST have gained widespread acceptance in clinical settings. These include the use of smaller endotracheal tubes, 11 topical or intravenous application of corticosteroids or local anesthetics, 12 , 13 ketamine gargle, 14 topical application of magnesium 15 and others. Dexmedetomidine, a selective α2-adrenaline receptor agonist, has a dose-dependent sedative effect on respiration with minimal depressive effects.…”
Section: Introductionmentioning
confidence: 99%